Ganoderma Neo-Japonicum Imazeki in Bu Gia Map National Park: Studies on Nutritional Compositions, Active Biological Compounds, and Antioxidant Properties - Hue Thi Ha,; Duong Nguyen Ma,; Minh Thi Thu Ta,; Hao Nhat Dinh,; Tuan Anh Hoang,; Sang Huy Vo,; Dao Thi Anh Phan, (Journal of Technical Education Science, 2025)
Ganoderma neo-japonicum Imazeki, 1939 is a special mushroom species growing on tropical bamboo bushes and has been used in folk medicine to prevent and treat many diseases. Our investigation provided valuable scientific evidence about nutritional composition, active biological compounds, and antioxidant properties, helping to evaluate this mushroom's medicinal value properly and contributing to the conservation and propagation of precious mushroom species in Bu Gia Map National Park. G. neo-japonicum contains a high total polysaccharide of 72.4 %, carbohydrate of 74 g/100 g, and high mineral contents like Na, Ca, and Mg. Additionally, the ethanol extract of G. neo-japonicum exhibits a substantial total polyphenol content, quantified at 284.91 mg GAE/mg DW, along with a total flavonoid content of 73.12 mg CAE/g DW and a total saponin content of 230.23 mg OAE/g DW. Consequently, this extract demonstrates potent antioxidant properties, evidenced by an IC50 value of 11.70 µg/mL in the DPPH assay and an EC50 value of 124.68 µg/mL in the FRAP assay. Interestingly, the presence of adenosine with a concentration of 104 mg/kg plays a significant role in using this mushroom in food and medicine because this is a bioactive compound found in Cordyceps mushrooms and has a variety of bioactivity such as possible cardioprotective and therapeutic agents for chronic heart failure.